2021
DOI: 10.5334/gh.988
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Shock Among Patients with and without Acute Myocardial Infarction in a Latin American Country: A Single-Institution Study

Abstract: Background: Latin America has limited information about the full spectrum cardiogenic shock (CS) and its hospital outcome. This study sought to examine the temporal trends, clinical features and outcomes of patients with CS in a coronary care unit of single Mexican institution. Methods: This was a retrospective study of consecutive patients hospitalized with CS in a Mexican teaching hospital between 2006-2019. Patients were classified according to the presence or absence of acute myocardial infarction (AMI). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Although it was demonstrated that increased cTN levels may increase the risk CS, very limited data are available focusing on the prognostic value of cTN levels in patients admitted with CS even though CS occurs in up to 10% of patients with AMI [ 52 , 53 ]. The association of cTNT levels in CS patients with concomitant VA-ECMO treatment was investigated by Li et al within 72 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was demonstrated that increased cTN levels may increase the risk CS, very limited data are available focusing on the prognostic value of cTN levels in patients admitted with CS even though CS occurs in up to 10% of patients with AMI [ 52 , 53 ]. The association of cTNT levels in CS patients with concomitant VA-ECMO treatment was investigated by Li et al within 72 patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, real-life studies enrolling patients with AMI typically include only minor part of patients suffering from AMIrelated CS. Of note, the incidence of non-AMI-related CS was shown to increase, 24 and moreover, specifically heart failure-related CS-mortality was shown to increase during the past decades despite overall improved CS-related mortality rates. 25 Less data is available investigating the prognostic value of platelet count in patients with CS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by González-Pacheco et al among non-AMI CS patients, valvular heart disease (49.3%) and cardiomyopathies (42.3%) constituted primary etiologies for the non-AMI CS. CS is often associated with organ failure, which can directly and indirectly impact the prognosis, including mortality 3 . A study by Vallabhajosyula et al reported 32.4% and 31.9% prevalence for single-organ and multi-organ failure, respectively, among AMI-CS patients 4 .…”
Section: Introductionmentioning
confidence: 99%